Faktor-Faktor yang Memengaruhi Ketepatan Waktu Kehadiran Mahasiswa pada Jam Kuliah Pertama di Fakultas Kedokteran Universitas Muslim Indonesia: Factors That Influence Students' Punitiveness Of Attendance During The First Lecture At The Faculty Of Medicine, Muslim University Of Indonesia - Artjan, Luthfiah Amelia; Amir, Suliati P.; Lantara, Andi Millaty Halifah Dirgahayu; Mochtar, Shulhana; Ismail, Muhammad Wirasto (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Punctual student attendance during early morning lectures plays a vital role in ensuring the effectiveness of learning, particularly in medical education, which demands high levels of discipline, academic workload, and mental readiness. However, student tardiness remains a common issue, influenced by various internal and external factors. This study aimed to analyze the factors affecting the punctuality of students’ attendance in the first lecture session at the Faculty of Medicine, Universitas Muslim Indonesia. A cross-sectional quantitative design was used with a total sample of 197 pre-clinical students from the 2022 cohort, selected through quota sampling. Data were collected using structured questionnaires covering six independent variables: internal factors (learning motivation, sleep quality, and subject interest) and external factors (teaching methods, weather conditions, and learning environment). Data were analyzed using multiple linear regression with SPSS software. The results showed that learning motivation (p = 0.045) and interest in the subject (p = 0.010) had a positive and significant effect on student attendance. Conversely, teaching methods (p = 0.005) and the classroom environment (p < 0.001) had a significant negative effect. Sleep quality (p = 0.257) and weather (p = 0.776) were not statistically significant. The regression model explained 48.7% of the variation in attendance (R² = 0.487). These findings emphasize the importance of both psychological and pedagogical factors in influencing student punctuality and highlight the need for engaging teaching approaches and supportive learning environments.